Metarhizium mendonceae sp. nov.: An important biological control agent for insect pests. - Jayara Dayany da Costa Silva; Paulo Roberto Ramalho Silva; Solange Maria de França; Ibrahim A Saleh; Francisco de Alcântara Neto; Mohamed A El-Tayeb; Kedma da Silva Matos; Mostafa A Abdel-Maksoud; Sarah da Silva Costa Guimarães; Alan Mario Zuffo; Gilvan Ferreira da Silva; Antônio Roberto Gomes de Farias; et al. (PLoS ONE)
The Metarhizium anisopliae complex consists of 34 formally described phylogenetic species. Metarhizium anisopliae sensu lato has been used for decades in Brazil as a biological control agent for controlling spittlebugs in sugarcane plantations. We investigated the identities of the Metarhizium isolates used in mycoinsecticide formulations through multilocus phylogenetic analyses and morphological characterization for species delimitation. A well-supported clade containing only isolates from this study formed a sister group with species of M. anisopliae sensu stricto, which we described as a new taxon, M. mendonceae sp. nov. Isolates URM 8144 and URM 8145 are used in the formulation of various brands of biological insecticides; however, they have always been referred to as M. anisopliae. According to the antibiosis assay, all the isolates of this new species were able to colonize and kill Mahanarva spectabilis nymphs. Therefore, M. mendonceae has been used in the formulation of mycoinsecticides for several decades under the name M. anisopliae.